2007
DOI: 10.1002/car.972
|View full text |Cite
|
Sign up to set email alerts
|

Working in partnership: user perceptions of intensive home visiting

Abstract: The aim of this study was to explore the perceptions of vulnerable women about the value of intensive home visiting in pregnancy and the first year of life delivered by health visitors trained to work in partnership with families.Twenty in-depth interviews were conducted with women who had completed the home visiting programme and agreed to be interviewed. The data were fully transcribed and analysed thematically.Despite initial concerns and negative preconceptions about health and social service professionals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 17 publications
6
36
0
Order By: Relevance
“…Whilst there may be some common thinking about the difficult things in parenting, the importance and priority of these difficulties can differ between health visitors and parents (Foster and Mayall, 1990;Bloomfield et al, 2005). Failure to read cues, or to purposively seek clarification of parents' understanding, risks damaging future opportunities for health promotion, as parents may feel they are being dictated to and misunderstood when presented with unsolicited advice (Bloor and McIntosh, 1990;Foster and Mayall, 1990;Kirkpatrick et al, 2007;McIntosh and Shute, 2007). This may be perceived as being judgemental (Roche, et al, 2005) or as 'negative verbal persuasion' (Bandura, 1982), which has the potential to undermine selfefficacy, whereas 'positive verbal persuasion' (praise, encouragement, support) can help it to develop.…”
Section: Shortcomings In Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there may be some common thinking about the difficult things in parenting, the importance and priority of these difficulties can differ between health visitors and parents (Foster and Mayall, 1990;Bloomfield et al, 2005). Failure to read cues, or to purposively seek clarification of parents' understanding, risks damaging future opportunities for health promotion, as parents may feel they are being dictated to and misunderstood when presented with unsolicited advice (Bloor and McIntosh, 1990;Foster and Mayall, 1990;Kirkpatrick et al, 2007;McIntosh and Shute, 2007). This may be perceived as being judgemental (Roche, et al, 2005) or as 'negative verbal persuasion' (Bandura, 1982), which has the potential to undermine selfefficacy, whereas 'positive verbal persuasion' (praise, encouragement, support) can help it to develop.…”
Section: Shortcomings In Practicementioning
confidence: 99%
“…In some instances, the health visitor may mediate between the parent and a third party (Bryans et al, 2009) and, when the parent accepts referral, the health visitor can support introductions to another source of help (Luker and Chalmers, 1989;Kirkpatrick et al, 2007). After identifying needs and resources, offering some follow-up can help the parent feel that they are valued and being kept in mind (Hanafin and Cowley, 2006;Worth and Hogg, 2000).…”
mentioning
confidence: 99%
“…A review of the published and grey literature indicated that while there was a heavy focus on program evaluation, the majority of evaluation reports do not include an investigation of clients' perspectives of intensive home visiting programs. There are five studies that have specifically investigated parents' perspectives of intensive nurse home visiting programs: two of these studies are from the United Kingdom (McIntosh & Shute, 2006;Kirkpatrick et al, 2007), two from Canada (Jack et al, 2005;Heaman et al, 2005) and one from the United States of America (DeMay, 2003). Five major themes were identified during the review of these studies, they included: negative preconceptions, trusting relationships, support, empowerment, and change.…”
Section: Program Evaluationmentioning
confidence: 99%
“…For participants, engaging in the program was an ongoing cyclical process that included When difficult messages are communicated with respect, they are likely to be accepted with respect (Kirkpatrick et al, 2007). Lack of respect and adversity especially in early childhood can result is low self-esteem or not valuing one's self, depression and abusive relationships in adulthood (Saunders, 2002).…”
Section: Discussionmentioning
confidence: 99%